Development and validation of a new asthma questionnaire to help achieve a high level of control in school-age children and adolescents - Matsunaga, Mayumi; Sato, Yasunori; Nagao, Mizuho; Ikeda, Masanori; Motomura, Chikako; Kameda, Makoto; Yoshida, Yukinori; Terada, Akihiko; Miyairi, Isao; Fujisawa, Takao (Allergology International, 2024)
Maintaining good asthma control minimizes the risk of exacerbations and lung function decline and is a primary goal of asthma management. The Japanese Pediatric Asthma Guidelines (JPGL) employs different classification criteria for control status from other guidelines, stressing a higher level of control. Based on JPGL, we previously developed a caregiver-completed questionnaire for assessing and achieving best asthma control in preschoolers. In this study, we aimed to develop a questionnaire for school-age children and adolescents. A working questionnaire comprising 14 items for patients and 34 items for caregivers was administered to 362 asthma patients aged 6–15 years and their caregivers. Separately, physicians filled out a questionnaire to determine JPGL-defined control. Logistic regression analysis was performed to construct a model to predict control levels using data from a randomly selected set of completed questionnaires from two-thirds of the subjects. Validation was performed using the remaining questionnaires. A set of 7 questions, encompassing self-assessed control status at the time of the visit and in the past month, and nocturnal/early morning asthma symptoms for patients and frequency of asthma symptoms, dyspnea, rescue beta-agonist use, and asthma hospitalization for caregivers, were selected and the 7-item model showed a good statistical fit with AIC of 110.5. The model has been named the Best Asthma Control Test for School Children and Adolescents (Best ACT-S). Best ACT-S scores differed significantly in the hypothetical direction among the groups of different JPGL-defined control levels, step-up/down treatment decisions, and presence/non-presence of exacerbations in the previous year. The Best ACT-S is a valid questionnaire for children/adolescents aiming for best asthma control.